STRATEGI PENGEMBANGAN PROGRAM PUBLIK MUSEUM BENTENG VREDEBURG YOGYAKARTA - , VINCENSIUS AGUS SULISTYA, Dr. Mahirta, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
research, education, and recreation. In the implementation of this, museum designs museum programs. One of the programs is museum for public program. Museum public program is a program held by the museum in order to increase the involvement of the community towards the museum. Besides, this program aims to increase the societyâs understanding towards museum, invite new visitors and re-invite the visitors to come again in the next chance. It is important to look for a suitable public program development for the museum. In 2006 until 2012 Museum Benteng Vredeburg Yogyakarta has develop a lot of public program in order to increase the involvement of the society. However, how far it reaches its goal as well as the vision and mission of the museum needs to be evaluated. The result of the evaluation from public program held by Museum Benteng Vredeburg Yogyakarta shows that improvement is needed to increase the involvement of the society. The expected impact of the public program held has not achieved. The position of public program to endorse the vision and mission of the museum needs to be increased. This research aims to find suitable strategy in order developing public program of Museum Benteng Vredeburg Yogyakarta. The analysis used this research is SWOT analysis. Considering the present of new paradigm in museum field, which is Paradigm Participation, this research aims to give strategy in developing public program that involve the society and increase the achievement of the museum vision and mission in the future.